2021
DOI: 10.3390/app11052426
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Synthesis of Metal–Matrix Composites (Ni-Ti)-TiB2

Abstract: Currently, metal–matrix composite materials are some of the most promising types of materials, and they combine the advantages of a metal matrix and reinforcing particles/fibres. Within the framework of this article, the high-temperature synthesis of metal–matrix composite materials based on the (Ni-Ti)-TiB2 system was studied. The selected approaches make it possible to obtain composite materials of various compositions without contamination and with a high degree of energy efficiency during production proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In addition, it was shown in [33] that chromium nitride decomposes at a temperature of 1770 • C into nitrogen and chromium. Comparing the obtained results with the data from [27,35], it can be assumed that endothermic processes occur in the CrN-TiNi samples through the incongruent melting of the CrN alloy with the evolution of nitrogen and melting of titanium. Then, temperature levelling occurs throughout the entire layer (area 3) and a further temperature decrease takes place, which is characteristic of the cooling of synthesis products.…”
Section: Investigation Of Combustion In the Crn-tini Mixture Samplerssupporting
confidence: 56%
See 3 more Smart Citations
“…In addition, it was shown in [33] that chromium nitride decomposes at a temperature of 1770 • C into nitrogen and chromium. Comparing the obtained results with the data from [27,35], it can be assumed that endothermic processes occur in the CrN-TiNi samples through the incongruent melting of the CrN alloy with the evolution of nitrogen and melting of titanium. Then, temperature levelling occurs throughout the entire layer (area 3) and a further temperature decrease takes place, which is characteristic of the cooling of synthesis products.…”
Section: Investigation Of Combustion In the Crn-tini Mixture Samplerssupporting
confidence: 56%
“…In combination with the data presented in [26,27,35], the results obtained from the investigation of the combustion processes in CrN-TiNi samples and the phase composition and structure of the synthesis products allowed us to suggest a mechanism of the formation of the CrNi-TiN composite. Figure 5 presents a diagram of the formation of SHS-produced CrNi-TiN materials in the process of the combustion of the CrN-TiNi powder mixture.…”
Section: Sample Of Thementioning
confidence: 65%
See 2 more Smart Citations
“…Due to the presence of ceramic inclusions in the metal-matrix composites, their properties (hardness, strength, operating temperatures, and oxidation resistance) are improved relative to traditional metallic materials [ 8 ]. In a previous study [ 9 ], we used the SHS method to obtain composite structured particles from (Ni-Ti)-TiB 2 powders. It was found that the particle structure consisted of an Ni-Ti intermetallic matrix, in which TiB 2 particles were uniformly distributed.…”
Section: Introductionmentioning
confidence: 99%